Why did the average duration of unemployment become so much longer? - Toshihiko Mukoyama; Aysegül Sahin (Federal Reserve Bank of New York, 2004)
This paper examines the causes of the observed increase in the average duration of unemployment over the past thirty years. First we analyze whether changes in the demographic composition of the U.S. labor force, particularly the age and gender composition, can explain this increase. We then consider the contribution of institutional changes, such as the change in the generosity and coverage of unemployment insurance. We find that changes in the composition of the labor force and institutional changes can only partially account for the longer duration of unemployment. We construct a job search model and calibrate it to U.S. data. The results indicate that more than 70 percent of the increase in the duration of unemployment over the past thirty years can be attributed to an increase in within-group wage inequality
Keywords: E24; J64; 330; Arbeitslosigkeit; Dauer; Bevölkerungsstruktur; Arbeitsplatzsuchmodell; Schätzung; USA